Kontribusi Tokoh-Tokoh Klasik Semantik Arab dalam Sejarah dan Perkembangan Ilmu Al-Dilalah - Sopyan, Yayan; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This study aims to analyze the contributions of classical Arab semantic scholars to the history and development of ?Ilm al-Dil?lah and to trace the relevance of their thought to modern semantic theory. Employing a literature review with a qualitative historical-analytical approach, the research examines the major works and ideas of Al-Far?h?d?, S?bawayh, Al-Jurj?n?, and Ibn Far?s through both classical and contemporary sources. The findings reveal that Al-Far?h?d? established the structural foundations of lexicography, S?bawayh expanded the grammatical-semantic dimension, Al-Jurj?n? constructed a relational theory through na?m, and Ibn Far?s developed a historical perspective through ta?awwur al-ma?n?. The intellectual legacy of these four figures played a pivotal role in shaping theories of meaning and lexical indication in modern Arabic linguistics. The study further recommends modifications to contemporary ?Ilm al-Dil?lah to make it more dynamic, integrative, and rooted in classical epistemology. The integration of classical traditions with modern approaches enables ?Ilm al-Dil?lah to evolve as a discipline that is relevant, contextual, and applicable in the fields of linguistics, Qur’anic exegesis, and contemporary Arabic language education.